Effect of premature luteinizing hormone surge on pregnancy outcomes in intracytoplasmic sperm injection or in vitro fertilization cycles - Aldarsooni, Maram; Alfarah, Mohammad; Albohammod, Fatimah; Al-Jaroudi, Dania (Frontiers in Medicine, 2025)
Background: A premature surge in luteinizing hormone (LH) during ovarian stimulation cycles between 12% to 25% has been commonly reported. However, there is still a lack of consensus whether premature LH surge affects pregnancy outcomes.Objective: To evaluate the effect of premature LH surge on pregnancy rate in women with and without premature LH surge during intracytoplasmic sperm injection or in-vitro fertilization cycles stimulation at a tertiary hospital in Riyadh, Saudi Arabia.A cross-sectional study was conducted. Information related to 771 women who had IVF/ICSI cycles between January 2022 till December 2022 was reviewed. The patients were divided into two groups based on premature LH surge.Results: There was no significant difference in the patient's characteristics. Live birth was significantly higher in the women without premature LH surge compared to women with LH surge (12.9% vs. 5.6%) (p=0.010). With regard to the number of oocytes collected, M2 and fertilization rate, it was significantly higher in the women without premature LH surge p-value 0.001, 0.002, 0.004, respectively).The study demonstrates significantly higher live birth rate in the women without premature LH surge.